2020
DOI: 10.1080/2162402x.2020.1761205
|View full text |Cite
|
Sign up to set email alerts
|

Tumors escape immunosurveillance by overexpressing the proteasome activator PSME3

Abstract: The success of CD8 + T cell-based cancer immunotherapy emphasizes the importance of understanding the mechanisms of generation of MHC-I peptide ligands and the possible pathways of tumor cell escape from immunosurveillance. Recently, we showed that peptides generated in the nucleus during a pioneer round of mRNA translation (pioneer translation products, or PTPs) are an important source of tumor specific peptides which correlates with the aberrant splicing and transcription events associated with oncogenesis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Accordingly, in vitro degradation with purified proteasomes of a long precursor (52mer) containing an embedded epitope sequence showed complete hydrolysis into small fragments of the antigenic peptides when 20S was associated with PA28γ, while in its absence generation of the epitope was clearly detectable. Consistent with these observations, knockout of PA28γ was found to negatively impact tumor growth in a mouse model, an effect that was partly dependent on the ability of PA28γ to impair the immunosurveillance process [131]. The ability of PA28γ to reduce MHC class I presentation and to counteract autoimmunity was also recently reported by Yao L. et al [135].…”
Section: Role In Immune Responsessupporting
confidence: 80%
See 3 more Smart Citations
“…Accordingly, in vitro degradation with purified proteasomes of a long precursor (52mer) containing an embedded epitope sequence showed complete hydrolysis into small fragments of the antigenic peptides when 20S was associated with PA28γ, while in its absence generation of the epitope was clearly detectable. Consistent with these observations, knockout of PA28γ was found to negatively impact tumor growth in a mouse model, an effect that was partly dependent on the ability of PA28γ to impair the immunosurveillance process [131]. The ability of PA28γ to reduce MHC class I presentation and to counteract autoimmunity was also recently reported by Yao L. et al [135].…”
Section: Role In Immune Responsessupporting
confidence: 80%
“…However, more recent studies pointed out that PA28γ has specific functions that are related to the proper functioning of the immune system. Overexpression of PA28γ was shown to markedly decrease MHC class I presentation of epitopes derived from PTPs (Pioneer Translation Products) in cancer cell lines, while its reduction leads to the opposite result [ 131 ]. PTPs are polypeptides produced in the nucleus by a non-canonical translation event prior to mRNA splicing and whose generation is specifically enhanced in cancers due to aberrant mRNA transcription and maturation processes that are typically associated with oncogenesis.…”
Section: Pa28γmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteasome activator subunit 3 (PSME3), a subunit of the 11SREG-γ proteasome regulator, is associated with the proteasome and is known to regulate the degradation of the cell cycle protein-dependent kinase inhibitors p21 and p16, the oncogene SRC-3 and the tumor suppressor p53 ( Li et al, 2007 ; Zhang and Zhang, 2008 ). In addition, recent studies have revealed that tumors evade immune surveillance by overexpressing PSME3 ( Boulpicante et al, 2020 ). It was proposed in previous studies that S100A6 acts as a calcium sensor and regulator to promote cellular calcium signaling and, in lung cancer, promotes cancer cell proliferation, invasion, and migration through P53 acetylation ( Emberley et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%